Anti-Mafia Code and 231 Models: An Opportunity for Improvement (?) (UNWE Yearbook, 2024)
The research aims to understand whether, and to what extent, there are currently suitable institutions for the implementation of prevention and restoration of legality in the corporate sphere in the Italian legal system. These, if properly applied, should enable the enterprise to transform a negative event, such as mafia infiltration in its various forms, into an opportunity for improvement itself. More specifically, an attempt will be made to assess the ability of institutions such as judicial administration (Art. 34 of the Anti-Mafia Code - Legislative Decree No. 159/2011), judicial control (Art. 34-bis), voluntary judicial control (Paragraph 6, Art. 34-bis), preventive cooperation (Art. 94-bis), and organizational and management models under Legislative Decree No. 231/2001 (so-called Models 231) adopted ex post facto to put the company back on the correct path of legality.